About the Effectiveness of the Training Technology Model of Trigonometry Teaching for the Mathematical Profile Students - N. I. Popov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to trigonometry teaching in higher school as a part of the elementary mathematics course with a complex hierarchical structure. Due to the complicated content of the given discipline,each of its modules can be divided into separate themes; though, the teacher should emphasize their interrelations, as well as the links with the coordinate method, geometry and mathematical analysis.The recommended training technology model allows the teacher to build up and control the training process, and achieve good results in accordance with the assigned tasks. In the course of the model approbation, theauthor developed the e-learning resource and identification method for selecting the key mathematical examples and exercises for each theme and module. The analysis of students' tests and questionnaires conducted for several years proves the effectiveness of the designed model for the senior university students of mathematical profile. Based on the research findings, the author developed the educational methodology complex for the Basics of Trigonometry course.